LEGAL DEVELOPMENT POLICY AND IDENTIFICATION OF LEGAL PROBLEMS (STUDY OF THE POSITION OF LAW IN DEVELOPMENT) - Yamin, Ahmad Fachri; Al Faraby, Ahmad Habib (P3M Stia Al Gazali Barru and Meraja media, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal